A randomized, controlled comparison of macroscopic conjunctival hyperemia in patients treated with bimatoprost 0.01% or vehicle who were previously controlled on latanoprost - E Randy Craven (Dove Medical Press, 2010)
E Randy Craven1, Ching-Chi Liu2, Amy Batoosingh2, Rhett M Schiffman2, Scott M Whitcup21Glaucoma Consultants of Colorado, Denver, CO, USA; 2Allergan, Inc., Irvine, CA, USA; This work was presented in part at the 19th Annual Meeting of the American Glaucoma Society (AGS); March 5–8, 2009; San Diego, CA, USAPurpose: To evaluate conjunctival hyperemia associated with bimatoprost 0.01% treatment in patients who replace latanoprost 0.005% with bimatoprost 0.01%.Methods: Randomized, double-masked, vehicle-controlled, multicenter study of patients with ocular hypertension or glaucoma whose intraocular pressure (IOP) was adequately controlled on latanoprost monotherapy. At baseline, patients discontinued latanoprost and were randomized to treatment with once-daily bimatoprost 0.01% (n = 151) or vehicle (n = 71). The primary endpoint was the peak change in macroscopic hyperemia (conjunctival hyperemia evaluated by gross visual inspection) from baseline to month 1.Results: Bimatoprost 0.01% was noninferior to vehicle in the mean [standard deviation] peak change from baseline macroscopic hyperemia at month 1 (0.18 [0.46] in the bimatoprost 0.01% group vs 0.02 [0.32] in the vehicle group, P = 0.009). The between-group difference was 0.15 (95% confidence interval [CI]: 0.04, 0.26), which was within the predefined margin for noninferiority of 0.5 on a hyperemia grading scale of 0 to +3. There were no statistically significant between-group differences in the percentage of patients with a ≥1-grade increase in macroscopic hyperemia from baseline. Mean IOP was decreased from baseline (-0.7 to -1.3 mm Hg) in the bimatoprost 0.01% group (P ≤ 0.002) and was increased from baseline (+3.3 to +3.6 mm Hg) in the vehicle group (P < 0.001) at month 1. There were no statistically significant between-group differences in adverse events.Conclusions: Bimatoprost 0.01% was noninferior to vehicle with respect to conjunctival hyperemia in this study population. Replacement of latanoprost with bimatoprost 0.01% in patients with ocular hypertension or glaucoma can result in additional IOP reduction without clinically important hyperemia.Keywords: conjunctiva, glaucoma, hyperemia, intraocular pressure, prostaglandin analogs, topical drug administration